Evaluation of perinatal maternal audit program (AMP) in the Langsa City - Fithriany, Fithriany; AS, Emilda; Mutiah, Cut; Dewi, Silfia; Harahap, Lili Kartika Sari; Rahayu, Sandy (Institute of Computer Science (IOCS), 2024)
The government has established the Neonatal Maternal Audit (AMP) program to assess the provision of health services to mothers and children, aiming to address obstetric and neonatal emergencies. Despite the implementation of AMP in Langsa City, the rates of maternal and infant mortality remain high. This study aimed to evaluate the AMP program in Langsa City. A cross-sectional survey research design was used, conducted at the Langsa City Health Office. The subjects of the study included the Mother and Child Program Holders at Puskesmas and hospitals, as well as the Maternal Perinatal Audit Program Implementation team at the Health Office. The findings revealed that the implementing team had an average tenure of 5 years, an average age of 38 years, and a D3 Midwifery education. They had received training on AMP and AMP-SR, possessed an AMP implementation manual, and conducted verbal autopsies, but only a few performed medical records. Strengthening materials and training on AMP-SR for program implementers in Langsa City is necessary. The implementation of the AMP program in Langsa City has shown positive aspects in terms of manpower and case selection, but areas requiring attention and improvement were also identified. Increasing the number of concurrent positions and providing comprehensive materials to program implementers will enhance their capabilities and effectiveness.